Work Environment, Stress Productivity, and the Mediating Effect of Job Satisfaction - Enzelina, Tiari; Dlyaulhak , Lulu; Nabillah , Sarah Ayudhia; Nurdiana, Editya (IJBLE Scientific Publications Community Inc., 2024)
This study set out to ascertain how work environment and stress affected productivity, with job satisfaction acting as a mediating factor. The purpose of this study was to improve the work productivity and job happiness of the nurses at Hasna Medika Hospital in Cirebon City. With the use of SmartPLS 3.0 software, this study employs quantitative data analysis techniques utilizing Structural Equation Modeling (SEM) based on Partial Least Square (PLS). At the Hasna Medika Hospital in Cirebon, 78 nurses were given questionnaires to complete in order to gather primary data. The findings demonstrated that job satisfaction was positively and significantly impacted by work stress. Furthermore, there was no discernible impact of the work environment or job stress variables on work productivity. Nonetheless, there is a sizable relationship between productivity and job satisfaction. The work environment and stress management are not the only factors that affect productivity and job happiness. Investigating additional factors that can help achieve this objective is crucial. These variables should be further investigated by researchers.